Rich variety of substrates for surface enhanced Raman spectroscopy. (5th July 2016) - Nguyen, Bich Ha; Nguyen, Van Hieu; Tran, Hong Nhung
Abstract: The efficiency of the application of surface enhanced Raman spectroscopy (SERS) technique to each specified purpose significantly depends on the choice of the SERS substrate with an appropriate structure as well as on its performance. Until the present time a rich variety of SERS substrates was fabricated. They can be classified according to their structures. The present work is a review of main types of SERS substrates for using in the trace analysis application. They can be classified into 4 groups: (1) Substrates using gold nanoparticles (AuNPs) with spherical shape such as colloidal AuNPs, AuNPs fabricated by pulsed laser deposition, by sputtering or by capillary force assembly (CFA), substrates fabricated by electrospinning technique, substrates using metallic nanoparticle arrays fabricated by electron beam lithography combined with CFA method, substrates using silver nanoparticle (AgNP) arrays grain by chemical seeded method, substrates with tunable surface plasmon resonance, substrates based on precies subnanometer plasmonic junctions within AuNP assemblies, substrates fabricated by simultaneously immobilizing both AuNPs and AgNPs on the same glass sides etc. (2) Substrates using nanostructures with non-spherical shapes such as gold nanowire (NW), or highly anisotropic nickel NW together with large area, free-standing carpets, substrates with obviously angular, quasi-vertically aligned cuboid-shaped TiO2 NW arrays decorated with AgNPs, substrates using gold nanoprism monolayer films, substrates using silver nanocube dimmers or monodisperse close-packed gold nanotriangle monolayers. (3) Substrates using multiparticle complex nanostructure such as nanoparticle cluster arrays, gold nanoflowers and nanodendrites. (4) Flexible substrate such as paper-based swab with gold nanorods, adhesive polymer tapes fabricated by inkjet printing method and flexible and adhesive SERS tapes fabricated by decorating AuNPs via the conventional drop-dry method.